EVALUASI PASCA HUNI ASPEK FUNGSIONAL PADA BANGUNAN RUMAH SUSUN SEDERHANA SEWA (RUSUNAWA) UNIVERSITAS TANJUNGPURA - O'i Prasesti; Muhammad Ridha Alhamdani; Rudiyono Rudiyono (JMARS: Jurnal Mosaik Arsitektur, 2021)
Policies and strategies for the construction of flats have been launched in various cities, one of which is in Pontianak which is intended for the general public and students. One of the Rusunawa in Pontianak is the Tanjungpura University Flat which is rented out for students which was built in 2009. Based on this, it is necessary to carry out a Post-Work Evaluation of the building that has been used for some time. This study aims to identify and evaluate the Rusunawa building of Tanjungpura University in terms of functional aspects and its application in design solutions. The research approach used is qualitative and quantitative research. The research method used is spatial syntax and place-centred mapping. The results showed that the results of connectivity analysis in spatial syntax showed low values in the drying room and kitchen area and integration analysis on spatial syntax showed low values in building circulation areas 1, 2, 3, and 4. Place centered mapping data showed activity. That residents routinely do on the building. This indicates a change in the function of space and affects the dimensions of space. The post-occupancy evaluation shows a change in the function of space, access to circulation, and the dimensions of space in the building. Based on the results of post-occupancy analysis and evaluation, the design proposal also focuses on variables with functional aspects, namely circulation, dimensions, flexibility and changes in space function.